Improve Knowledge Visualization through an Interactive Graph-based Dashboard System with Key Performance Indicator: A Case Study of University Dashboard for Higher Education - Wan Maseri, Wan Mohamad (2007)
We propose a novel approach of knowledge visualization technique by generating knowledge through a graph-based clustering technique, incorporating tacit knowledge and finally visualizing the knowledge in dashboard form. Three aspects are emphasized: clustering technique, knowledge visualization and domain knowledge interaction. Clustering technique with the feature vectors helps user to mine data from the enterprise database for pattern recognition. The knowledge visualization helps users to analyze the comprehensive characteristics of the objects under study. Subsequently, domain knowledge interaction shall enable the human’s perceptual capabilities to be transferred, thus increases the intelligence of the system. The knowledge visualization is enhanced through the dashboard concept which incorporated with Key Performance Indicator where it provides significant patterns of knowledge on real-world. The framework consists of the knowledge visualization model and a prototype system design for higher education environment is presented in this paper.